Pengaruh Dimensi Kualitas Pelayanan terhadap Kepuasan Pasien pada Jaringan Klinik Anak Perusahaan BUMN: Analisis Multilevel - Suryo Andrianto; Cindyana Gunawan (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2026)
The purpose of this study was to examine the effects of healthcare personnel services, service time, service conformity, clinic facilities, and administration and registration on patient satisfaction while accounting for patients nested within clinics. The method used a quantitative analysis of de-identified secondary survey data collected from January to December 2025, comprising 2,740 patients from 17 clinics in a State-Owned Enterprise subsidiary clinic network. A two-level linear mixed model with a clinic random intercept was estimated using restricted maximum likelihood. The results showed that the null-model intraclass correlation coefficient was 51.17%. In the full model, service conformity had the strongest positive effect (b = 0.399; p < 0.001), followed by clinic facilities (b = 0.041; p = 0.001). Healthcare personnel services, service time, and administration and registration were not significant. Between-clinic variance declined by 55.76%, although the remaining random intercept was significant (p = 0.008). The conclusion is that expectation fulfillment and clinic facilities should be prioritized, while persistent between-clinic differences require unit-specific quality improvement. Keywords: Clinic Network, Multilevel Analysis, Patient Satisfaction, Secondary Data, Service Quality